Water Quality Index of Fresh Water Streams Feeding Wular Lake in Kashmir Himalaya- India (International Journal of Innovative Research in Engineering & Management, 2022)
This study aimed to analyze the impact of  water quality on living beings especially on aquatic life and those who use it for drinking purposes. The  preliminary analysis of the data showed that water quality  indexes are rising year to year in wular lake. Further, the  analysis showed that the water quality parameters are more  effective to aquatic life ,because the aquatic life needs  more water for living.The main areas which are polluting  the water are industries,using of fertilizer and pesticides  also use of chemicals in paints. Similarly, the waste water  of villages and towns is less effecting in increasing the  water indexes as compared to the industrial waste  water.The main pollutants are dying industries,use of  unwanted medicines in plants are causing sevier problems  in water. During construction usage of oils also cause these  problems in increasing the water quality parameters. The  water of the lakes are getting effected due to these wastes  , because the wular lake is the main fresh water lake in  Kashmir india. Maximum people of valley are using it in  drinking purposes. They are getting effected by this unclen  water. Due to this the chest prolems are created due to  which the water of wular lake had became the main  problem causing agent in population. Results are showing  the bad effect on population and aquatic life,because the  aqualtic species are indirectlt effectin on humans. By  eating fishes and nuts of wular lake. Based on these results,  we conclude that reduction in water quality parameters is  a major concern because day by day the industries are  increasing the waste and it is directly effective in  increasing the parameters , government should to take  immidate steps to save this fresh water lake. As a result,  the government should devise strategies to reduce harmful  water quality parameters which are causing main effect to  living population. Environmental protection is a long  process requiring ongoing planning, government  regulations, and public and industrial participation. To  decrease these parameters everyone should be involved in  this matter, it is abig concern future generation.
Keywords: Water Quality Index; How To Overcome From This Problem; Decreasing Agents; Main Causicative Agents